2020
DOI: 10.15408/sjie.v9i1.12899
|View full text |Cite
|
Sign up to set email alerts
|

Central Bank Independence and Inflation: The Matters of Financial Development and Institutional Quality

Abstract: The inverse relationship between the independence of the central bank (CBI) and inflation became a consensus that trusted throughout the world. However, there is no conclusive explanation of why and how central bank independence has succeeded in suppressing inflation. The purpose of this study is to examine the influence of financial development and institutional quality on the relationship between central bank independence and inflation. Using 20 Countries of Asia with institutional diversity, this study anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…On the other hand, a study conducted for 20 Asian countries empirically confirmed that the consequence of increased central bank independence is an increase in the level of inflation measured by the GDP deflator (Kunaedi & Darwanto, 2020). In addition, it is determined that the current level of inflation is determined by its previous value.…”
Section: Literature Reviewmentioning
confidence: 98%
“…On the other hand, a study conducted for 20 Asian countries empirically confirmed that the consequence of increased central bank independence is an increase in the level of inflation measured by the GDP deflator (Kunaedi & Darwanto, 2020). In addition, it is determined that the current level of inflation is determined by its previous value.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The central bank will construct its inflation targeting framework (ITF) to take steps to bring the inflation level within the acceptable range (Setiartiti & Hapsari, 2019). The more independent a central bank is in enforcing its duties, the more able it becomes to limit the negative impact of inflation (Kunaedi & Darwanto, 2020). Therefore, in devising the right monetary policy, the central bank must be able to forecast the inflation occurring in the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Економісти А. Кунайді та Д. Дарванто критично розглянули постулат про обернену кореляцію між незалежністю ЦБ та інфляцією, яка стала консенсусом, котрому довіряли в усьому світі [14]. Вони визнали, що немає однозначного пояснення, чому та як незалежність ЦБ дала можливість стримати інфляцію.…”
unclassified